Mitigating Paxlovid™-induced drug‒drug interaction toxicity: an in silico insight - Ta, Giang H.; Leong, Max K. (Frontiers in Pharmacology, 2024)
The clinical drug-drug interaction side-effects of Ritonavir, an ingredient in Paxlovid TM , have been documented, highlighting the need to explore alternative administration methods for Nirmatrelvir, another drug in the Paxlovid TM combination. In this study, the skin permeability potential of Nirmatrelvir was assessed using various in silico models. The prediction results suggest that Nirmatrelvir could be administrated via the transdermal route, offering a promising avenue to enhance the efficacy of anti-COVID-19 agents.